Empirical Evidence on Dividends as a Signal of Firm Value - Eades, Kenneth M. (Journal of Financial and Quantitative Analysis, 1982)
Kenneth M. Eades, Empirical Evidence on Dividends as a Signal of Firm Value, The Journal of Financial and Quantitative Analysis, Vol. 17, No. 4, Proceedings of the 17th Annual Conference of the Western Finance Association, June 16-19, 1982, Portland, Oregon (Nov., 1982), pp. 471-500